FASILITAS HOTIMART AGRO CENTER SEBAGAI DAYA TARIK WISATAWAN DI KABUPATEN SEMARANG - Desika Nur Jannah (Journal of Tourism Destination and Attraction, 2021)
Tourism is also a human need. Tourism can be both refreshing and educational. The purpose of this study was to determine 1) the main facilities provided as a tourist attraction; 2) supporting facilities provided as a tourist attraction; and 3) complementary facilities provided as a tourist attraction for the Hortimart Agro Center. The research method used qualitative by using observation, interview, and documentation data collection techniques. The data analysis technique used a qualitative description. The results showed that: (1) the main facilities as a tourist attraction of Hortimart Agro Center regarding cleanliness are sufficient, comfort is sufficient, and beauty is satisfactory or good; (2) supporting facilities as a tourist attraction for the hortimart agro center regarding accommodation that is sufficient, where to eat meets, parking area is fulfilling, where for shopping is fulfilling, and transportation is fulfilling; and (3) complementary facilities as a tourist attraction hortimart agro center regarding sufficiently adequate toilets, meeting places of worship, satisfying tour guides, and adequate information centers.